2021
DOI: 10.26682/sjuod.2021.24.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Study of Acinetobacter Baumannii Using 16s Rrna And Bla Oxa-51 Gene Isolated from Hospitals in Duhok-kurdistan Region, Iraq

Abstract: Background and objective: Acinetobacter baumannii is pathogenic and multiresistant bacteria that cause nosocomial infection. The aim of this study are diagnosis A. baumannii by using specific bla OXA-51 and 16SrRNA. Methods: out of 150 Acinetobacter species samples were collected from patients in Azadi teaching hospital, Duhok Emergency hospital; and burn Duhok cosmetic and burn hospital from May 2020 to August 2020. The samples were phenotypically diagnosed by bacteriological strategy. Out of 100 samples were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
1
2
1
Order By: Relevance
“…In the present work, 58% of the isolates showed resistance to carbapenem (CRAB) by the Kirby-Bauer disc diffusion susceptibility testing, and among these CRAB isolates, carbapenemase activity was detected by the RAPDEC Carba NP and Meropenem+EDTA CDT tests in 88.8% and 55%, respectively. which was inconsistence with studies conducted recently in Sulaimani city [15] and in Duhok city [16], furthermore, high resistance to carbapenems reported in Iran 94% in 2020 [12], 99% in 2021 [24] and in Jordan 75.1% in 2022 [39]. To determine the role of efflux pump activity, we used EP inhibitor (CCCP) to observe the reduce in the sensitivity of the tested isolates toward meropenem, the MIC was reduced by at least fourfold in the presence of 25µg/mL CCCP in 22.5% (7/31) of all isolates and 38.8% (7/18) among CRAB isolates.…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…In the present work, 58% of the isolates showed resistance to carbapenem (CRAB) by the Kirby-Bauer disc diffusion susceptibility testing, and among these CRAB isolates, carbapenemase activity was detected by the RAPDEC Carba NP and Meropenem+EDTA CDT tests in 88.8% and 55%, respectively. which was inconsistence with studies conducted recently in Sulaimani city [15] and in Duhok city [16], furthermore, high resistance to carbapenems reported in Iran 94% in 2020 [12], 99% in 2021 [24] and in Jordan 75.1% in 2022 [39]. To determine the role of efflux pump activity, we used EP inhibitor (CCCP) to observe the reduce in the sensitivity of the tested isolates toward meropenem, the MIC was reduced by at least fourfold in the presence of 25µg/mL CCCP in 22.5% (7/31) of all isolates and 38.8% (7/18) among CRAB isolates.…”
Section: Discussioncontrasting
confidence: 94%
“…These enzymes are intrinsic and naturally exist in the chromosomal DNA of A. baumannii inherited into all strains. This fact makes it a wonderful marker successfully applied for the detection of A. baumannii at the species level [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study found resistance to imipenem (96%) and meropenem (94%) by the disc diffusion approach. Clos to this study's findings, a previous study in Dohuk by Qader (2021) reported that 80% and 90% of isolates exhibited resistance to imipenem and meropenem, respectively. However, Smail and AL-otrachi ( 2020) found a higher rate of resistance (100%) to the above-mentioned antibiotics in a study performed in Erbil.…”
Section: Discussionsupporting
confidence: 65%